2016
DOI: 10.1007/s00158-016-1411-8
|View full text |Cite
|
Sign up to set email alerts
|

Designing meta material slabs exhibiting negative refraction using topology optimization

Abstract: This paper proposes a topology optimization based approach for designing meta materials exhibiting a desired negative refraction with high transmission at a given angle of incidence and frequency. The approach considers a finite slab of meta material consisting of axis-symmetric designable unit cells subjected to an exterior field. The unit cell is designed to achieve the desired properties based on tailoring the response of the meta material slab under the exterior field. The approach is directly applicable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…It should also be pointed out that the developed topology optimization framework involving the derivable LC and Mie resonances is not restricted to the double negative metamaterials presented here. In principle, the design strategy proposed here can be universal for all types of AMMs demanding negative constitutive parameters, whether they are double-negative (Yang et al, 2013;Brunet et al, 2015), single-negative (Fang et al, 2006;Lu et al;Shen et al, 2015) or even hyperbolic (Christensen et al, 2012;Shen et al, 2015;Christiansen et al, 2016). The present optimized AMMs and superlens provide the subwavelength imaging with the powerful and heuristic components, pushing the concept design to the specific practical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be pointed out that the developed topology optimization framework involving the derivable LC and Mie resonances is not restricted to the double negative metamaterials presented here. In principle, the design strategy proposed here can be universal for all types of AMMs demanding negative constitutive parameters, whether they are double-negative (Yang et al, 2013;Brunet et al, 2015), single-negative (Fang et al, 2006;Lu et al;Shen et al, 2015) or even hyperbolic (Christensen et al, 2012;Shen et al, 2015;Christiansen et al, 2016). The present optimized AMMs and superlens provide the subwavelength imaging with the powerful and heuristic components, pushing the concept design to the specific practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by the burgeoning 3D printing, topology optimization have successively accomplished the metamaterials design and then reached the desired performances (Otomori et al, 2012(Otomori et al, , 2017Sanchis et al, 2013;Dong et al, 2017Dong et al, , 2018Christiansen et al, 2016;Yang et al, 2018;Wang et al, 2018). Since AMMs have showed the unprecedented functionalities on wave manipulations, several topology optimization studies of AMMs are subsequently reported in recent years Lu et al;Christiansen et al, 2016). However, these works focus on the optimization of propagation responses (Christiansen et al, 2016) or positive wave parameters .…”
Section: Introductionmentioning
confidence: 99%
“…Topology optimization [21] was originally developed in the late 1980's for applications within solid mechanics [75]. Since the early 2000's, the method has been successfully applied to wave-governed design problems, such as acoustics [76,77,78], sub-wavelength antennas [79], nano-photonics [80,81,82], and plasmonics [83,84,2]. The wide adoption is attributable to the method's versatility, a growing numerical toolbox as well as advances in nanoscale production Because of this voxel-based description, the design is allowed to change during the optimization process without any predefined geometrical constraints, such as those imposed by parameter-based shape and size optimization.…”
Section: Topology Optimizationmentioning
confidence: 99%
“…Such an indirect method requires a large amount of computation labor and does not provide physical insight into the principle of DZIPnCs. Thus, in order to improve the computation efficiency in this case, several inverse-design cases based on optimization algorithms have been attempted recently 16 18 . To the best of our knowledge, however, an inverse design of a DZIPnC has not been reported.…”
Section: Introductionmentioning
confidence: 99%